A study on the determinants of teacher retention in Chinese primary schools in Johor, Malaysia - Chong, Jack Yee; Kong, Zao Yi; Sang, Jun Yao; Wong, Li Wen (2023)
It has been discovered that Malaysia faces the same difficulties with teacher retention as other nations throughout the world, namely the failure of teacher recruiting and job retention, which leads to teacher retention. Hence, the primary objective of this research is to examine the many factors that influence teacher retention in primary schools located in Johor, Malaysia. The major aim of this study is to ascertain the determinants that influence teacher retention rates within Chinese primary schools located in Johor, Malaysia. This study will examine several independent variables, including work environment, emotional demand, teacher self-efficacy, and work engagement. Furthermore, the study included a sample of 123 male and 238 female participants, representing 34% and 66% of the total respondents, respectively. These participants were selected from Chinese primary schools in Johor, Malaysia. This report utilizes the SPSS software to perform descriptive analysis, scale measurement, and inference analysis on the findings of the present investigation. These findings revealed statistically significant associations among the several independent variables examined, including work environment, emotional demand, teacher self-efficacy, and work engagement, with the dependent variable of teacher retention. This study gives future researchers some substantial insights and ways to improve their investigative reports.